General synthesis of CoCeMOx trimetallic oxides via a cation exchange reaction for the oxygen evolution reaction. Issue 16 (29th March 2023) - Huang, Xianggang; Wang, Xin; Liu, Yingxin; Hou, Yan; Li, Chengjin; Cai, Mingyang; Gu, Hongwei; Cao, Xueqin
Abstract : This article provides a general ion exchange and calcination method for sythesizing CoCeMO x, and demonstrates CoCeZnO x PNs exhibit the best electrocatalytic performance among them due to their higher content of oxygen vacancies and Co 2+ . Abstract : Cobalt-based spinel oxides are considered potential candidates for the oxygen evolution reaction (OER) due to their abundant valence changes and promising electrochemical activity, but their low intrinsic activity hinders their practical applications. Herein, we synthesize a series of CoCeMO x (M = Zn, Ni, Ru, Er, Mg, Mn, Sn) derived from CoCeM coordination-driven self-assembled aggregates (CDSAAs) using a general ion exchange and subsequent calcination method. Interestingly, CoCeMO x exhibit different morphologies from porous nanospheres, particle-stacked nanospheres, to hollow nanospheres as the third metal element is altered. Markedly, CoCeZnO x porous nanospheres (PNs) exhibit the best OER performance. The XPS results reveal that the existence of CeO2 and Zn 2+ ions significantly increased the Co 2+ /Co 3+ ratio and the content of oxygen vacancies in Co3 O4 . Furthermore, Co 2+ can be used as highly reactive sites to form CoOOH and the high content of oxygen vacancies can optimize the oxygen-containing intermediate adsorption energy, both of which can effectively improve the OER performance. Therefore, well-designed CoCeZnO x PNs demonstrate high OER activity with a lower overpotential ( η = 333 mV) than that of commercial RuO2 (344 mV) in 10 mA cm −2, a Tafel slope of 98 mV dec −1, and a long-term durability of 45 h. This work may provide some inspiration for the design of trimetallic oxide nanomaterials.